Encouraging ethical behaviour in public administration by human resource management - Dvoráková, Zuzana (Journal of Business Economics and Management, 2005)
The public administration reform in the Czech Republic set off with a reform of the territorial public administration at the end of the 90s. The reform established a joint public administration model in the territories, power decentralization, and de‐concentration of operative functions from ministries to regions and municipalities. The reform outcomes largely depend on the quality of human resources in public administration, their ethical values, and status in the society. The public sector always needs to solve a traditional ethics dilemma whether public officials serve citizen or politician purposes. The paper is aimed at ethical values in the Czech public administration, ethics dilemmas in the public sector, and human resource management in territorial self‐governments supporting ethical behaviour. An abnormal situation comes into being in the Czech Republic as public officials incline to serving neither citizens nor politicians. Some municipal authorities strive to improve public administration ethics by designing and implementing new HR practices, codes of ethics and anticorruption programmes.First published online: 14 Oct 2010